Governance of the Regional Healthcare System on the Example of Adjara Autonomous Republic - Gorgiladze, Nino (Caucasus Journal of Health Sciences and Public Health, 2020)
Based on strategic management, ensuring a comprehensive policy is an essential element for the development of the healthcare system. It is important to carry out strategic and targeted health policy at the regional level to provide equally accessible and high-quality medical services, in which the regional healthcare system performs the most significant part. In terms of governance structure, Georgia is a regionally organized, the exception is the Autonomous Republics, with an independent government and, accordingly with the Ministry of Health and social affairs, one of the main functions of which is to implement unified state health policy of Georgia. For this purpose, it is important that the guidelines of the Ministry of Health and Social Affairs of Adjara Autonomous Republic comply with the rights and responsibilities imposed on it; and that the structure is in line with the competencies provided for in the regulations. This analytical paper is an attempt, based on the study of the relevant regulatory framework, to review the functions of the healthcare system of the Autonomous Republic of Adjara as a governing body, to study and determine the compliance of the roles performed by the Ministry of Health and Social Affairs of Adjara with the imposed and designated duties. Based on the analysis of the studied material, we shall identify technical and content insufficiencies. Hypothesis: There is a structural-functional mismatch between central and regional health systems. The purpose of the paper was to study and determine the compliance of the functions performed by the Ministry of Health and Social Affairs of the Adjara Autonomous Republic with the imposed and delegated rights and responsibilities. During the research, were studied and processed the documents reflecting the state structure of Georgia, state management mechanisms, the state structure of the Health System management and the health policy; legal documents issued by the Government of Georgia and the supreme and executive bodies of the Autonomous Republic of Adjara; relevant regulatory documents for the management of the central and regional health care systems; Guidelines of the Ministries of Health of Georgia and Adjara; Textbooks of various authors and other information found on the Internet. To process the obtained materials, systematic, structural-functional and comparative-legal research methods were used. Based on the studied documents, a comparative analysis of the central and regional healthcare systems was made in the structural-governance context, based on the conclusion obtained as a result of the discussion, recommendations were developed.